Unusual presentation of appendicitis as soft tissue infection of the thigh. Issue 1 (9th January 2021) - Bryan, J; Ashcroft, J; Hudson, V E; Wong, K Y
Abstract: Appendicitis remains one of the most common causes of abdominal pain across the world typically presenting with right iliac fossa pain, fever and nausea or vomiting. We describe an unusual case of appendicitis presenting as a soft tissue infection of the thigh, thereby causing a delayed diagnosis from presentation. We discuss the pathophysiological process behind soft tissue infections caused by appendicitis and highlight investigation and management strategies to ensure prompt treatment to reduce patient mortality.